Ch’nook Indigenous Business Education Initiative - Colbourne, Rick (Journal of Aboriginal Economic Development, 2012)
This article focuses on the need for business education that is relevant to Aboriginal youth and senior leaders. It describes Ch'nook, an organization that provides support for post-secondary Aboriginal business education across three generations of participants. First, senior Aboriginal leaders and entrepreneurs who need business training (Aboriginal Management Certificate Program); second, post-secondary students enrolled in British Columbia (and soon Canada) by providing them with scholarships, bursaries, mentoring and internship opportunities (Indigenous Business Education Network/Ch'nook Scholars); and, third, it promotes business as a viable career option for Aboriginal high school students (Ch'nook Cousins). Ch'nook's efforts led to the signing of the British Columbia Indigenous Business Education Accord with the province's twenty-five colleges and universities and it has a cooperative agreement with four British Columbia universities. Ch'nook supports Aboriginal students in part by supplementing their studies with a strong Aboriginal perspective and context, which is often missing from their home institution's business programs. Working with community, business, and academic partners, Ch'nook promotes business as a viable career choice for Aboriginal participants and supports them in graduating from management and business education studies.